The Impact of Time on Nutrition and Health Claims on the Irish Marketplace - Stefanie Marisa Offe; Loanne Bebin; Fiona Lalor (Foods, 2022)
Since the implementation of Regulation (EC) No 1924/2006 on nutrition and health claims (NHCR) made on food, only 261 health claims have been authorised, suggesting that the regulation creates challenges for the food industry. This study looks at the prevalence of nutrition and health claims labelled on food on the Irish market. Specifically, we compared their prevalence in 2009 with those present on the marketplace in 2022. Food labels of defined food categories were examined in three nationwide supermarkets in Ireland, and data of claims made on these labels were collected. A series of statistical analyses was conducted to compare the results from 2021 with those of 2009. In 2021, around half of the examined products (52.8%) displayed at least one nutrition claim, showing no significant difference with the data collected in 2009 (53.5%). Individual categories, however, did exhibit changes between the two time points. The prevalence of health claims on food has decreased from 21.6% in 2009 to 10.5% in 2021. There will always be a time lag between when a regulation is enacted and what its true impact can be measured. This study provides these data for the impact of time on EU Regulation 1924/2006 on the Irish market.